Appraisal and discernment of prevalent drug-drug interactions in patients with psychiatric disorders - Jacob, Axa; Thomas, Cristin Simon; Deore, Anay; Deshpande, Prasanna (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Drug-drug interactions (DDIs) contribute majorly to hospital admissions, treatment failures, avoidable medical complications and subsequent healthcare costs. Thus, we employ a mechanistic approach to prospectively investigate the incidence of potential DDIs in the psychiatric patients in a clinical setting. Methods: In this prospective, observational, multi centred study conducted for a span of 6 months, psychiatric inpatients (≥18 years) prescribed with 2 or more medications daily for any medical illness were included. The secured prescriptions of the inpatients selected in accordance to the inclusion criteria were then assessed for DDIs using Micromedex(TM) as a standard. Results: Of the total 400 enrolled participants, 383 (95%) of them showed at least one pDDI regardless of the severity. An average of 7.33 interactions per patient was also deduced. A high prevalence of pDDIs totalling to 2900 was recorded in our study with an average of 7.33 interactions per patient. Most of the interactions were of major (56.52%) and moderate severity (39.07) followed by contraindicated (2.55) and minor (1.83). Cardiovascular system (41.77%) had the highest potential to be affected due to the pDDIs identified. Trihexyphenidyl, haloperidol, promethazine, amisulpride, risperidone, divalproex, trifluoperazine, olanzapine and clozapine where among the most commonly encountered drugs in these interactions. Conclusions: A high prevalence of pDDIs totalling to 2900 was recorded in our study with an average of 7.33 interactions per patient. A significant association of the pDDIs with variables such as age, gender, diagnosis and total number of drugs used was identified. More studies are required to explore the overall pattern of DDIs in psychiatric patients along with their levels and correlation with different risk factors. Careful monitoring and documentation are necessary to prevent further complications thereby improving the therapeutic outcome.